Surviving the COVID-19 Pandemic: Surge Capacity Planning for Nonemergent Surgery. Issue 2 (August 2020) - Squitieri, Lee; Chung, Kevin C.
Abstract : Summary: The coronavirus disease 2019 (COVID-19) pandemic has confronted the U.S. health care system with unprecedented challenges amidst a tenuous economic environment. As inpatient hospitals across the country prepare for an overwhelming influx of highly contagious COVID-19 cases, many nonemergent procedures have been cancelled or indefinitely postponed without guidance regarding eventual safe accommodation of these procedures in the future. Given the potentially prolonged impact of the COVID-19 pandemic on health care use, it is imperative for plastic surgeons to collaborate with other medical and surgical specialties to develop surge capacity protocols that allow continuation of safe, high-quality, nonemergent procedures. The purpose of this article is to provide necessary and timely public health information relevant to plastic surgery and also share a conceptual framework to guide surge capacity protocols for nonemergent surgery.